Electrocatalytic alcohol oxidation by a molecular iron complex. (17th February 2022) - Kuiry, Himangshu; Das, Debasree; Das, Soumadip; Chakraborty, Soham; Chandra, Bittu; Gupta, Sayam Sen
Abstract : An efficient electrochemical method for the selective oxidation of alcohols to their corresponding aldehydes/ketones using a biomimetic iron complex, [(bTAML)Fe III –OH2 ] −, as the redox mediator in an undivided electrochemical cell with inexpensive carbon and nickel electrodes using water as an oxygen source is reported. Abstract : An efficient electrochemical method for the selective oxidation of alcohols to their corresponding aldehydes/ketones using a biomimetic iron complex, [(bTAML)Fe III –OH2 ] −, as the redox mediator in an undivided electrochemical cell with inexpensive carbon and nickel electrodes using water as an oxygen source is reported. The substrate scope also includes alcohols that contain O and N heteroatoms in the scaffold, which are well tolerated under these reaction conditions. Mechanistic studies show the involvement of a high-valent Fe V (O) species, [(bTAML)Fe V (O)] −, formed via PCET (overall 2H + /2e − ) from [(bTAML)Fe III –OH2 ] − at 0.77 V ( vs. Fc + /Fc). Moreover, electrokinetic studies of the oxidation of C–H bonds indicate a second-order reaction, with the C–H abstraction by Fe V (O) being the rate-determining step. The overall mechanism, studied using linear free energy relationships and radical clocks, indicates a "net hydride" transfer, leading to the oxidation of the alcohol to the corresponding aldehyde or ketone. When the reaction was carried out at pH > 11, the reaction could be carried out at a ∼500 mV lower potential than that at pH 8, albeit with reduced reaction rates. The reactive intermediate involved at pH > 11 is the corresponding one-electron oxidized [(bTAML)Fe IV (O)] 2− species.